Ethnic differences in diurnal cortisol profiles in healthy adults: A meta‐analysis. Issue 4 (27th June 2019) - Boileau, Kayla; Barbeau, Kheana; Sharma, Rupali; Bielajew, Catherine
Abstract : Purpose: Cortisol is a well‐known biomarker of the physiological stress system; atypical cortisol patterns have been linked to many psychological and physiological illnesses. Previous studies have found vast health disparities among ethnic groups; however, studies examining the relationship between cortisol and ethnicity have found mixed results. This meta‐analysis investigated whether there are differences in diurnal cortisol outcomes among ethnic groups, while considering the moderating roles of various individual factors and methodological approaches. Methods: Search phrases were entered into MEDLINE, PsycINFO, EMBASE, Cochrane Library, CINAHL, Scopus, and Web of Science. Effect sizes were extracted for ten diurnal cortisol outcomes, including waking, 30 min after waking, cortisol awakening response, slope, area under the curve, urinary twenty‐four‐hour secretion, total cortisol output, and midday, evening, and bedtime concentrations, for eight ethnic group comparisons, including Asians, Blacks, Hispanics, Indigenous people, Whites, Minority and Majority groups, and Multiethnic groups. Moderator analyses, including variables such as gender, age, and number of cortisol collection time points, were conducted. Results: There were significant ethnic differences in diurnal cortisol profiles, including cortisol awakening responses, with more robust differences in ethnic comparisons that included White participants. Differences in diurnal cortisol profiles were also moderated by gender, mean age, and sample size. Conclusions: This meta‐analysis supports the notion that ethnic groups exhibit distinct diurnal cortisol profiles, which, according to the biopsychosocial model of health, may be a result of unique sociocultural experiences. The limitations of this meta‐analysis and future directions for stress research with various ethnic groups are discussed. Statement of contribution What is already known on this subject? Studies have found vast health disparities among ethnic groups. Psychological and physiological illnesses and atypical diurnal cortisol profiles are strongly correlated. Studies have examined the relationship between diurnal cortisol rhythms and ethnicity, but findings are mixed. What does this study add? This study is a systematic examination of the relationship between diurnal cortisol rhythm and ethnicity. Psychosocial and methodological factors moderate the relationship between diurnal cortisol output and ethnicity. This study provides insight on factors that contribute to health disparities among ethnic groups.